Odpowiedzi

Najlepsza Odpowiedź!
2010-04-15T15:53:36+02:00
X+y/2 -1 = x-y/6 / obustronnie mnozymy przez 6
x+y/2 - x-y/3= -2 /obustronnie mnozymy przez 6

3(x+y) - 6 = x-y
3(x+y) - 2(x-y) = -12

3x+3y-x+y=6
3x+3y -2x+2y= -12

2x+4y=6
x+5y=-12 / mnozymy przez -2

2x+4y=6
-2x-10y=24

-6y=30
y=-5

2x+4*(-5)=6
y=-5

2x-20=6
y=-5

x=13
y=-5



2010-04-15T15:57:32+02:00
{x+y/2 - 1 = x-y/6 /6
{x+y/2 - x-y/3 = -2 /6

6(x+y)/2-1*6=6(x+y)/6
6(x+y)/2-(6(x-y))/3=-2 *6

3x+3y-6=x+y
3x+3y-2x+2y=-12

3x+3y-x-y=6
x+5y=-12

2x+2y=6
x+5y=-12 /-2

2x+2y=6
-2x-10y=24

-8y=18
y=18/-8
y= -2 ,25

x=-12-5*(-2,25)
x=12-(-11,25)
x=23.25

x=23,25
y=-2,25